Comparing contemporaneous hunter-gatherer and early agrarian settlement systems with spatial point process models: Case study of the Estonian Stone Age. (February 2022) - Sikk, Kaarel; Caruso, Geoffrey; Rosentau, Alar; Kriiska, Aivar
Highlights: Quantitative comparison of settlement systems with first order point process models. Usable area by Corded Ware culture increased compared to hunter-fisher-gatherer. Larger usable land made possible the migration of early agrarian society. Overlap of suitable residential areas could have led to competition for space. Spatial land use structure was more homogeneous for early agrarian population. Differing model performance can be caused by social structure or land-use patterns. Abstract: Inductive locational models have been used for decades to map the probability of past settlements and identify the preferred environmental conditions for habitation. In this study we apply inductive modelling to compare the spatial structure of the settlement systems of hunter-fisher-gatherer groups (Narva and Combed Ware Culture) and early agrarian communities (Corded Ware Culture) in Stone Age Estonia. We conceptualise settlement system formation as a point process and develop a first order point process model representing the environmental suitability for habitation based on geomorphological, soil and proximity to water. We use MaxEnt and the SDMTune machine learning framework for building the model, variable selection and estimation. The model is applied to the two communities and the effects of the variables and the resulting spatial patterns compared. The statistical analysis indicated higher predictive power for hunter-fisher-gatherer sites, which might result from higher variety of agrarian activities, different socio-economic organization or effects of spatial structure of the landscape. The spatial comparison indicates significant differences between the suitable environments for habitation between the two groups. While the hunter-fisher-gatherer population had an entirely shoreline connected settlement system the Corded Ware people inhabited the areas further away from water bodies. This resulted in significantly expanded potential space with differing spatial configuration for the incoming agrarian groups, possibly allowing tolerated immigration. The results also indicate there was a certain overlap of areas considered suitable habitation by both cultural groups, which might have caused a competition for land.